ON THE EXPERIENCE OF USING A BIOLOGICALLY ACTIVE FOOD ADDITIVE IN THE NUTRITION OF ATHLETES - Тухтаров Бахром Эшназарович; Jibin Thomas (Galaxy International Interdisciplinary Research Journal, 2024)
The development of ways to increase the biological usefulness of athletes’ diets by using the protein source Nogliukin. The results of the research have established that in professional athletes, the use of dietary supplements for Nogliukin food normalizes the biochemical indicators of the nitrogenous components of urine and improves the digestibility of protein